Pride, Shame, and Group Identification - Salice, Alessandro; Montes Sánchez, Alba (Frontiers in Psychology, 2016)
Self-conscious emotions such as shame and pride are emotions that typically focus on the self of the person who feels them. In other words, the intentional object of these emotions is assumed to be the subject that experiences them. Many reasons speak in its favor and yet this account seems to leave a question open: how to cash out those cases in which one genuinely feels ashamed or proud of what someone else does? This paper contends that such cases do not necessarily challenge the idea that shame and pride are about the emoting subject. Rather, we claim that some of the most paradigmatic scenarios of shame and pride induced by others can be accommodated by taking seriously the consideration that, in such cases, the subject “group-identifies” with the other. This is the idea that, in feeling these forms of shame or pride, the subject is conceiving of herself as a member of the same group as the subject acting shamefully or in an admirable way. In other words, these peculiar emotive responses are elicited in the subject insofar as, and to the extent that, she is (or sees herself as being) a member of a group – the group to which those who act shamefully or admirably also belong. By looking into the way in which the notion of group identification can allow for an account of hetero-induced shame and pride, this paper attempts to achieve a sort of mutual enlightenment that brings to light not only an important and generally neglected form of self-conscious emotions, but also relevant features of group identification. In particular, it generates evidence for the idea that group identification is a psychological process that the subject does not have to carry out intentionally in the sense that it is not necessarily triggered by the subject’s conative states like desires or intentions.